Percursos identitários de formadores de professores: o papel do contexto institucional, das diferentes áreas do conhecimento e das disciplinas - Dotta, Leanete Teresinha Thomas (2010)
This work aims to concentrate its investigation in the field of teaching formation and, more specifically, the teacher educators in undergraduate courses of teachers formation. In accordance to a sociological perspective, we seek the understanding of the teaching professional identities of teacher educators, emphasizing some of their constitutive processes. The main objective of this investigation is to learn and analyze the teaching professional identities of teacher educators in undergraduate courses of teachers formation, which are built from the administrative and academic organization of the institutions where they work, from the subjects they teach and from the field of knowledge of the course they work at. As theoretical-methodological references in the field of professional identities we used Claude Dubar and Amélia Lopes s contributions. In the teaching field of the university education, the basis for the discussions was extracted from Maria Isabel da Cunha, Lee Shulman, Miguel Zabalza and Carlos Marcelo, among others. To proceed with the data collection, put into practice in 2008 and 2009, we used semistructured interviews with twenty teachers from undergraduate courses of teachers formation in: History, Mathematics, Physical Education and Pedagogy. Two teachers from each course were randomly selected one who was in charge of teaching specific subjects and the other who used to teach subjects related to the teachers formation, from two campuses of a state university, from one campus of a private university and two private colleges, located in the eastern region of the state of Paraná in Brazil. Analyzing the data, according to the theoretical references, it was possible to realize the crucial role, in the subjects identity constitution, of the following aspects: initial formation and institutional dynamics where the former happened; specificities of the work context, according to the kind of institution; relations with the significant others. In the teachers who were subjects of this study, the double negotiation between the formation in its subjective/biographical nature and the work context in its objective/relational nature resulted in identities marked by continuity and recognition